New species and records of cunaxid mites (Acari: Cunaxidae) from soil in Southern Brazil - Rocha, Matheus Dos Santos; Rodrigues, Everton Nei Lopes; Ferla, Noeli Juarez (Zootaxa, 2015)
Neocunaxoides promatae sp. nov., Bonzia flechtmanni sp. nov. and Dactyloscirus multiscutus sp. nov. are described from soil and leaf litter in Atlantic rainforest and Atlantic Araucaria forest in natural environments in São Francisco de Paula municipality, Rio Grande do Sul State, Brazil. In addition, the species Pulaeus quadrisolenidius Castro & Den Heyer 2009 and Lupaeus lectus Castro & Den Heyer (2009) are registered for the first time in this State.